2004
DOI: 10.1128/jb.186.13.4262-4275.2004
|View full text |Cite
|
Sign up to set email alerts
|

Autoinduction ofBacillus subtilis phoPROperon Transcription Results from Enhanced Transcription from EσA- and EσE-Responsive Promoters by Phosphorylated PhoP

Abstract: The phoPR operon encodes a response regulator, PhoP, and a histidine kinase, PhoR, which activate or repress genes of the Bacillus subtilis Pho regulon in response to an extracellular phosphate deficiency. Induction of phoPR upon phosphate starvation required activity of both PhoP and PhoR, suggesting autoregulation of the operon, a suggestion that is supported here by PhoP footprinting on the phoPR promoter. Primer extension analyses, using RNA from JH642 or isogenic sigE or sigB mutants isolated at different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
53
0
3

Year Published

2005
2005
2012
2012

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(58 citation statements)
references
References 41 publications
2
53
0
3
Order By: Relevance
“…In B. subtilis, the well characterized phoPR promoter region contains five different starts which respond to 285 different environmental stimuli, some of them constitutive but enhanced by PhoP~P (phosphorylated PhoP) binding (Paul et al 2004). Constitutive low expression of the S. coelicolor phoRP promoter region in a similar manner is very plausible since a basal level of PhoR-PhoP ready to be activated when phosphate is scarce must be available within the cell.…”
Section: Advantages 275mentioning
confidence: 97%
“…In B. subtilis, the well characterized phoPR promoter region contains five different starts which respond to 285 different environmental stimuli, some of them constitutive but enhanced by PhoP~P (phosphorylated PhoP) binding (Paul et al 2004). Constitutive low expression of the S. coelicolor phoRP promoter region in a similar manner is very plausible since a basal level of PhoR-PhoP ready to be activated when phosphate is scarce must be available within the cell.…”
Section: Advantages 275mentioning
confidence: 97%
“…Many two-component systems are transcribed from more than one promoter: for example phoPQ in Salmonella typhimurium (Soncini et al, 1995), bvgAS of Bordetella pertussis (Scarlato et al, 1990) and phoPR in Bacillus subtilis (Paul et al, 2004). This strategy allows for differential usage and regulation of promoters under diverse environmental conditions to facilitate bacterial adaptation.…”
Section: Discussionmentioning
confidence: 99%
“…For genes classified as both Pho and E E regulon genes, the mechanism responsible for inclusion of the phoPR promoter has been explained by PhoPϳP amplification of A -and E -responsive phoPR operon promoters (35). Here we showed that the PhoP-regulated phoB promoter, P V , is a A promoter and that transcription from the second promoter, P S, requires only E E , although the P S transcription was delayed in a phoPR mutant (Fig.…”
Section: Discussionmentioning
confidence: 72%
“…The putative yycOP and glnQ promoters are interesting in that both contain two putative consensus repeats for a PhoP dimer binding site on the coding strand on either side of the Ϫ35 element of the putative E promoter. It should be interesting to determine if E E -responsive PhoP-activated genes exist (in addition to autoregulation) and if their requirement for PhoP binding is different than the requirement for all PhoP-activated A promoters studied (13) or for the PhoP-enhanced autoregulation E E promoter (35).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation